Mulheres negras: tradições orais, artes, ofícios e identidades - Marcelino, Jacqueline Laranja Leal (2016)
From a comparative perspective, the orality of the African traditions and the arts / works are analyzed as constituents of the identities of black women, protagonists of the novels: The Color Purple (1986), by Alice Walker (African-American); Ponciá Vicêncio (2003), by Conceição Evaristo (Afro-Brazilian); and Niketche: a history of polygamy (2004), by Paulina Chiziane (African of Mozambique). Gender and ethnicity issues are privileged, contextualized and problematized with the support of historical reference, of feminist and postcolonial studies. The selected narratives and their protagonists tangentiate themselves through memories of slavery and / or colonization that impacted the African and their descendants, but not only that. It is understood that representations of oralities in the three narratives indicate the appreciation of the characters for the return to the past as a form of self-knowledge, and for the preservation of their origins and traditions as a form of resistance. The correlation between black women and their everyday arts and works, in its turn, mark a know-how transmitted from generation to generation. These constituents have a strong connection with memory and ancestry, but without essentialization; the characters need to know their origins in order to (re) elaborate their identities with this basis and strength.